Pupuk Alami dari Dapur Sendiri: Kreasi Pupuk Organik Cair dari Kulit Buah - Indah Nur Latifah; Hariyati Hariyati; Desy Puspitasari; Diyah Ayuningsih; Eka Dwi Cahyo Nugroho; Farida Fadlilah; Febrianti Nurul Hidayah; Fitriana Nurjanah; Isma Febilla Ayuning Tyas; Ismila Yuliana Sari; Kartika Sari Nurbaiti; Vita Istihapsari; Syariful Fahmi; Agus Supriyanto (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2026)
Household organic waste remains a serious problem in Indonesia, particularly in urban areas that produce large amounts of waste. The inadequate utilization of kitchen waste, such as vegetable scraps and fruit peels, leads to environmental pollution and potential health problems. Independent waste processing into liquid organic fertilizer is an environmentally friendly solution that is effective and applicable using fermentation solutions. This program aims to educate and foster knowledge and skills in making liquid organic fertilizer from kitchen waste. This community service activity was carried out in Dukuh Lemusir, Pabelan Village, Kartasura Regency, targeting 19 women from the Family Welfare Movement (PKK) as the main partners (divided into 5 groups). The implementation included preparation, outreach, training, monitoring, and evaluation. Evaluation through questionnaires measured knowledge and skills analyzed using quantitative descriptive methods. The training focused on hands-on practice in making liquid organic fertilizer, conducted in groups with intensive guidance. The fermentation results were observed for approximately 30 days and indicated a successful process with characteristics such as brown color, a distinctive fruity aroma, an acidic pH, and no mold. The evaluation results showed an average achievement of 93.68%, categorized as very good. Contributing to reducing waste and environmental pollution, the use of liquid organic fertilizer also supports organic farming and reduces dependence on chemicals. This education and training is expected to encourage the sustainability of environmentally friendly waste management practices in the community and strengthen the government's integrated waste management program.